Respostas

2013-12-08T11:05:12-02:00
Para Y(X)=X2-4X+3
 x_{v} = \frac{-b}{2a} = \frac{4}{2.1} =2
 y_{v} = \frac{-delta}{4a} = \frac{-4}{4.1} =-1
V(2,-1)
para F(X)=X2+16
tex] x_{v} [/tex]= \frac{-b}{2a} = \frac{0}{2.1} =0
 y_{v} = \frac{-delta}{4a}=[tex] \frac{64}{4.1} =16
v(0,16)

Para y(x)=2X2-4X+2
 x_{v} = \frac{-b}{2a} = \frac{4}{2.2} =1
 y_{v} = \frac{-delta}{4a} =[tex] \frac{0}{4.2} =0
V(1,0)

ParaF(X)=X2-2X
 x_{v} = \frac{-b}{2a} = \frac{2}{2.1} =1
 y_{v} = \frac{-delta}{4a} =[tex] \frac{-4}{4.1} =-1
V(1,-1)


1 5 1